Pengaruh modal, tenaga kerja, dan bahan baku terhadap hasil produksi (studi kasus pabrik sepatu PT. Kharisma Baru Indonesia) - Dwi Nila Andriani (Universitas PGRI Madiun, 2017)
Shoes industry is an industry that has opportunities and market prospects are good. Shoes are one of the products that are not only intended for domestic demand but also developed for export.Therefore, as one of the shoes PT. Kharisma Baru Indonesia tried to do the production effectively and efficiently by allocating factors of production owned. This study aims to determine the influence factors of production, capital, labor, and raw materials to the production of PT Kharisma Baru Indonesia. Data collection techniques in this research is interview and documentation. The results showed that the partial factors of production, capital, labor, and raw materials significantly affect production. While simultaneously, three independent variables significantly affect production.